Perkembangan Motif Batik Jepara Tahun 2008-2019: Identitas Baru Jepara Berbasis Kearifan Lokal - Siti Maziyah; A. Alamsyah; Agustinus Supriyono (Department of History, Faculty of Humanities, Diponegoro University, 2020)
Along with the emergence of batik in various places with their respective regional identities, batik also emerged in Jepara with its characteristic motifs. This article aims to determine the development of Jepara batik motifs in 2008-2019 as Jepara's new identity based on local wisdom. The emergence of Batik Jepara has begun in 2008 that became the new identity of Jepara. This identity is further strengthened through the inauguration of batik as a world heritage object by UNESCO in 2009. This study uses literature, observation, and in-depth interview with batik entrepreneurs in Jepara to find out superior motifs and philosophies of each batik motif originating from the local wisdom of the people of Jepara. This identity is what makes Jepara batik motifs different from batik motifs in other places. The results show that the Jepara batik motif was influenced by the local culture of the Jepara community, that is not separated from the Jepara carving motif, Kartini batik motif, Jepara community legend, Jepara typical building icons, marine flora-fauna motifs that gave Jepara identity as a coastal area, and the existence of development motifs that remain based on the characteristics of Jepara.